Cardiovascular effects of 16 weeks of martial arts training in adolescents - Saraiva, Bruna Thamyres Ciccotti [UNESP]; Ritti-Dias, Raphael Mendes; Farah, Breno Quintela; Suetake, Vinícius Yukio Botelho [UNESP]; Diniz, Tiego Aparecido; Costa Júnior, Paulo [UNESP]; Milanez, Vinícius Flávio; Christofaro, Diego Giulliano Destro [UNESP] (FapUNIFESP (SciELO), 2018)
Introduction: Sedentary habits increase the chances of developing cardiovascular disease. Physical activity is one of the means of prevention and treatment of these diseases, thus martial arts represent a dynamic option in promoting physical activity. Objective: The objective of the study is analyze the effects of 16 weeks of Martial Arts (Muay Thai or judo) training on cardiovascular variables in adolescents. Methods: The sample consisted of 40 adolescents, aged 11 to 14 years, divided into two groups: Martial Arts (n=28) and control (n=12). Weight and height measurements were taken to calculate body mass index. Systolic and diastolic blood pressure (BP), heart rate (HR) at rest, pulse pressure (PP) and rate-pressure product (RPP), were also measured. The intervention was carried out through Martial Arts (Muay Thai and judo) training held twice a week for 90 minutes, over 16 weeks. The control group did not undergo any training. The statistical analysis was performed using the following tests: Shapiro-Wilks, Levene’s, analysis of covariance (ANCOVA), eta-squared effect size and the net-effect, using SPSS 15.0 software and a significance level of 5%. Results: There was no statistical difference between the control and Martial Arts groups for the sample characterization. There was a significant difference in systolic BP in the Martial Arts group when compared with the control group (p-value=0.049). The effect size can be considered moderate (effect size=0.163), with a good net-effect (3.4 mmHg). Conclusion: This study showed that 16 weeks of Martial Arts decreased systolic BP in normotensive adolescents. Level of Evidence II; Therapeutic studies - Investigating the results of treatment.
Efectos cardiovasculares de 16 semanas de entrenamiento de artes marciales en adolescentes
Efeitos cardiovasculares de 16 semanas de treinamento de artes marciais em adolescentes
Keywords: Adolescent; Arterial pressure; Blood pressure; Heart rate; Martial arts; Pulse pressure